2013
DOI: 10.3390/coatings3020108
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Interface Characteristics on the Adhesion/Cohesion of Plasma Sprayed Tungsten Coatings

Abstract: Abstract:Tungsten is the prime candidate material for plasma facing components of future fusion devices. Plasma spraying, with its ability to coat large areas, including non-planar surfaces, with a significant thickness, is a prospective fabrication technology for components subject to moderate heat loads, e.g., the first wall of the Demonstration Reactor (DEMO). The functionality of such coatings is critically dependent on their adhesion to the underlying material. This in turn, is influenced by a variety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…For instance, Takadoum and Bennani reported that titanium nitride (TiN) thin films deposited on rough steel substrates have poor adhesion [1]. In other cases, surface roughness has been shown to increase adhesion and cohesion between plasma-sprayed coatings and substrates [2,3]. For microelectronic applications, surfaces of Indium tin oxide (ITO) films should be atomically smooth to avoid electrical leakages; in fact, for such applications the interface width should be ~ 1 nm [4], [5].…”
Section: Introduction mentioning
confidence: 99%
“…For instance, Takadoum and Bennani reported that titanium nitride (TiN) thin films deposited on rough steel substrates have poor adhesion [1]. In other cases, surface roughness has been shown to increase adhesion and cohesion between plasma-sprayed coatings and substrates [2,3]. For microelectronic applications, surfaces of Indium tin oxide (ITO) films should be atomically smooth to avoid electrical leakages; in fact, for such applications the interface width should be ~ 1 nm [4], [5].…”
Section: Introduction mentioning
confidence: 99%
“…Hence, we stored our PDMS bioscaffolds in de-ionized water immediately after oxygen plasma treatment. As oxygen plasma treatment makes the PDMS surface rough [22] and brittle [56], it has the advantage of increasing the bonding strength between a coating layer and the underling PDMS bioscaf-fold [57]. Furthermore, the addition of another layer on top of the oxygen plasma treated PDMS surface has also been shown to prevent its hydrophobic recovery by mechanically stabilizing the surface [56].…”
Section: Discussionmentioning
confidence: 99%
“…Several FGM fabrication techniques were reviewed in [21]. The tungsten-steel bonding can be achieved by a number of techniques, including those using a third material as a bonding interlayer, instead of an FGM [22,23].…”
Section: Other Techniquesmentioning
confidence: 99%